Variation in Immunohistochemical Expression of Neuropilin1 among Oral, Laryngeal and Skin SCC - Khaled J Abed; Wassan H Younis (College of Dentistry/ University of Baghdad, 2017)
ABSTRACT Background: Neuropilin 1(NRP1) is considered a novel non - tyrosine kinase co- receptor for the vascular endothelial growth factors (VEGF). First discovered on migrating neurons. NRP1is suggested to be up-regulated in cells of different types of cancer and implicated with advanced disease. The aim of this study was to investigate the variation in expression of NRP1 in oral, laryngeal and skin squamous cell carcinoma. Materials and methods: Tissue sections from 120 formalin fixed- paraffin embedded blocks histopathologically diagnosed as oral, laryngeal and skin SCC (40 blocks for each),immunohistohemically stained in immunoperoxidase method with monoclonal antibodies to NRP1, the localization of expression was examined and the resulting scores were analyzed according to age, sex, and histopathological grades. Results: The immunohistochemical analysis revealed that the NRP1 expression in oral, laryngeal and skin squamous cell carcinoma was (87.5%), (92.2%) and (82.5%) respectively, with no significant variation in expression among them(P=0.44), but, NRP1 up-regulation in all the three types correlated positively with degree of differentiation (P=0.009), (P=0.002) and (P=0.007) respectively. Conclusion: Angiogenesis play an important and similar role in carcinogenesis of oral, laryngeal and skin squamous cell carcinoma, and NRP1 is significantly associated with degree of differentiation in the three types of carcinomaso it can be act as a prognostic marker.